Comparison of Clinical Characteristics, Laboratory Findings and Imaging Manifestations of COVID-19 in Sulfur Mustard-exposed Survivors and Others: a Case-control Study - Hosseiniara, Reza; Hosseini, Seyed M. J.; Mirhosseini, Seyed A.; Swann, Jennifer; Nodoushan, Majid Mirzaei; Sharti, Mojtaba; Nezhad, Hamidreza Ebrahimi; Amanpour, Hassan; Shahriari, Maryam; Farnoosh, Gholamreza; Farajzadeh, Mohsen Abbasi; Farahani, Alireza Jalali (Current Drug Therapy, 2021)
Objective: The objective of this study is to determine if previous exposure to sulfur mustard (SM) gas increases the pathogenesis of COVID-19 by comparing clinical characteristics, laboratory findings, and imaging data between SM-exposed survivors and other patients with COVID-19. Methods: This case-control study was conducted in Baqiyatallah hospital, Tehran, Iran, from 26th Feb – 26th March 2020. The case group composed of 60 SM-exposed survivors infected with COVID-19, and the control group was composed of 60 patients with COVID-19. Groups were matched for demographic (including age and gender) and comorbidity variables except for lung disease which was higher in the case group. The clinical characteristics, laboratory findings, and imaging manifestations, as well as outcomes, were compared between the two groups. Results: While the majority of patients in the case and control groups had at least one comorbidity like diabetes, hypertension, or heart disease, only lung disease was significantly higher in the case than in the control group (P=0.001). Patients in both groups displayed a variety of symptoms on arrival. Only chest pain was significantly more frequent in case patients than those in the control group. The levels of Neutrophils, ESR, BS, AST, LDH, and CRP in both groups were higher, and Na levels were lower than the normal range. Neutrophils were significantly higher in the case than in the control group (p=0.02). The BUN level was significantly lower in the control than in the case group (p=0.04). Other laboratory findings were within their normal ranges and similar in both groups. Significantly more patients in the case group showed early-stage opacities than those in the control group (p=.03). There were no significant differences in treatment or outcomes between the two groups. Conclusion: Most clinical characteristics, outcomes, and laboratory findings of COVID-19 in SMexposed survivors, were similar to those in the non-exposed. While these findings suggest that sulfur mustard gas exposure does not significantly affect the prognosis of the disease, the limitations and sample size of the current study may warrant additional investigations.
Keywords: COVID-19